Resin composition, and cured product, prepreg, printed wiring board, and high-frequency electronic component using same
By using a resin composition containing a polysenol resin with a specific group at the end and a compound containing an isocyanuric acid ring structure and an allyl group, combined with a thermoplastic resin, an inorganic filler and a curing catalyst, the problem of oxidation deterioration of thermosetting polysenol at high temperatures is solved, and the heat resistance reliability and dielectric characteristics of the resin composition are improved.
Patent Information
- Application Number
- CN202380058119.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-09
- Filing Date
- 2023-07-26
- Publication Date
- 2025-03-21
AI Technical Summary
The existing thermosetting polystyrene alcohol is prone to oxidation and deterioration at high temperatures, resulting in a significant change in the tangent of the dielectric loss (tanδ) value, affecting its heat resistance reliability.
A resin composition is used which has a polysenol resin having a specific group at the end and a compound containing an isocyanuric acid ring structure and an allyl group in the molecule, and a thermoplastic resin, an inorganic filler and a curing catalyst are added to the resin composition to improve its heat resistance and buried properties.
The resin composition has excellent heat resistance reliability, small change rate of dielectric loss tangent (tanδ) and good flowability, and is suitable for cured substances, prepregs, printed wiring substrates and high-frequency electronic components.
Smart Images

Figure CN119677789A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, and a cured product, a prepreg, a printed wiring board, and a high-frequency electronic component using the same. Background Art
[0002] In recent years, the communication speed of communication electronic devices (electronic substrates) such as smartphones, tablets, and communication base stations has been continuously improved, and the construction of 5G communication networks has been continuously promoted. With the increase in communication speed, in order to achieve low loss of electrical signals on substrates used in communication electronic devices, there is a significant demand for low dielectric materials and multi-layered substrates with high integration. In order to achieve this requirement, low dielectric resin substrates, ceramic substrates, and low dielectric interlayer adhesives are used.
[0003] As a material used in the adhesive layer, cover layer, substrate, etc. of a multilayer printed wiring board for high frequency use, it is known to use thermosetting polyphenylene ether (for example, refer to Patent Document 1). From the viewpoint of reactivity and solubility in solvents, the thermosetting polyphenylene ether is preferably low-molecular-weight, and is preferably a vinyl compound (having a vinyl functional group). Prior art literature Patent Literature
[0004] Patent Document 1: International Publication No. 2008 / 018483 Summary of the invention Technical Problems to be Solved by the Invention
[0005] However, the present inventors have found that a cured polyphenylene ether obtained by reacting a thermosetting polyphenylene ether having a vinyl group as a functional group is very susceptible to oxidative degradation at high temperatures and has a problem in that the value of the dielectric loss tangent (tan δ) varies greatly in terms of heat resistance reliability.
[0006] The present invention is an invention completed in view of the problems of such prior art. The present invention provides a resin composition with excellent heat resistance reliability (in other words, a small rate of change of dielectric loss tangent (tan δ)). Further, the present invention provides a cured product, a prepreg, a printed wiring board and a high-frequency electronic component using such a resin composition. Technical means to solve technical problems
[0007] According to the present invention, there are provided the following resin compositions, cured products, prepregs, printed wiring boards, and high-frequency electronic components.
[0008] [1] A resin composition comprising: (A) a polyphenylene ether resin having a group represented by the following formula (1) at the terminal, and (B) A compound having an isocyanuric acid ring structure and two allyl groups in one molecule and being liquid at 25°C.
[0009] [Chemistry 1] (Wherein, in the formula (1), R 1 represents a hydrogen atom or an alkyl group. )
[0010] [2] The resin composition according to the above [1], wherein the component (B) is a compound represented by the following formula (2).
[0011] [Chemistry 2] (Wherein, in the formula (2), R 2 It is an alkyl group having 4 to 14 carbon atoms.
[0012] [3] The resin composition according to [1] or [2], further comprising (C) a thermoplastic resin having a number average molecular weight of 30,000 or more.
[0013] [4] The resin composition according to [3] above, wherein the component (C) is a thermoplastic elastomer having a dielectric loss tangent (tan δ) of less than 0.005 in a frequency range of 1 GHz to 100 GHz.
[0014] [5] The resin composition according to [3] or [4] above, wherein the resin composition contains 20 to 80 parts by mass of the component (C) based on 100 parts by mass of the total resin components.
[0015] [6] The resin composition according to any one of [1] to [5] above, further comprising (D) an inorganic filler.
[0016] [7] The resin composition according to the above [6], wherein the resin composition contains 50% by mass or more of the component (D) based on 100% by mass of non-volatile components in the resin composition.
[0017] [8] The resin composition according to [7] above, wherein the resin composition contains 60% to 90% by mass of the component (D) based on 100% by mass of non-volatile components in the resin composition.
[0018] [9] The resin composition according to any one of [1] to [8] above, further comprising (E) a curing catalyst.
[0019]
[10] The resin composition according to any one of [1] to [9] above, wherein the resin composition contains 10 to 50 parts by mass of the component (A) based on 100 parts by mass of the total resin components.
[0020]
[11] The resin composition according to any one of [1] to
[10] above, wherein the resin composition contains 3 to 40 parts by mass of the component (B) based on 100 parts by mass of the total resin components.
[0021]
[12] A cured product of the resin composition according to any one of [1] to
[11] above.
[0022]
[13] A prepreg using the resin composition according to any one of [1] to
[11] above.
[0023]
[14] A printed wiring board comprising a cured layer composed of the resin composition according to any one of [1] to
[11] above.
[0024]
[15] A high-frequency electronic component comprising the cured product according to
[12] . Beneficial Effects
[0025] The resin composition of the present invention has the effect of excellent heat-resistant reliability (in other words, the rate of change of dielectric loss tangent (tan δ) is small). Further, the resin composition of the present invention is also good in fluidity, so the embedding property of the substrate is good, and has excellent film-forming property. Therefore, the resin composition of the present invention can be applicable to cured product, prepreg, printed wiring substrate and high-frequency electronic components, etc.
[0026] Furthermore, the cured product, prepreg, printed wiring board and high-frequency electronic component of the present invention use the above-mentioned resin composition of the present invention and have the effects of being excellent in dielectric properties, heat resistance and embedding properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] [ Figure 1 ] is a plan view showing patterning in the evaluation of substrate pattern embedding properties. [ Figure 2 ] is a photographic example of a case where the embedding property is good in the evaluation of the embedding property of the substrate pattern. [ Figure 3 ] is a photographic example of a case where the embedding property is poor in the evaluation of the embedding property of the substrate pattern. DETAILED DESCRIPTION
[0028] The following are embodiments of the present invention, but the present invention is not limited to the following embodiments. Therefore, it should be understood that, within the scope of the gist of the present invention, based on the common sense of those skilled in the art, the following embodiments are appropriately changed, improved, etc., and also belong to the scope of the present invention.
[0029] [Resin composition] One embodiment of the resin composition of the present invention is a resin composition comprising: (A) a polyphenylene ether resin having a group represented by the following formula (1) at the terminal, and (B) a compound having an isocyanuric acid ring structure and two allyl groups in one molecule and being liquid at 25° C. Hereinafter, (A) a polyphenylene ether resin having a group represented by the following formula (1) at the terminal is sometimes referred to as the (A) component. Similarly, (B) a compound having an isocyanuric acid ring structure and two allyl groups in one molecule and being liquid at 25° C. is sometimes referred to as the (B) component.
[0030] [Chemistry 3] (Wherein, in the above formula (1), R 1 represents a hydrogen atom or an alkyl group. )
[0031] The high frequency characteristics, heat resistance and heat-resistant reliability of the resin composition of the present embodiment are excellent. In addition, excellent heat-resistant reliability refers to the small change of the dielectric loss tangent (tan δ) in the heat-resistant reliability test. For example, as an example of excellent heat-resistant reliability, it can be cited that after being placed for 1000 hours under an environment of 125°C, the rate of change of the dielectric loss tangent (tan δ) is small compared with before being placed. Further, the resin composition of the present embodiment is also good in embedding property to the substrate because of its good fluidity.
[0032] The polyphenylene ether resin as component (A) has a group shown in the above formula (1) at its end, which can improve the above-mentioned heat resistance and heat resistance reliability. The present inventors have successfully developed a resin composition with excellent dielectric properties and excellent heat resistance, as a resin composition used in an adhesive layer, a cover layer, a substrate, etc. of a multilayer printed wiring board for high-frequency use (for example, Japanese Patent Application No. 2021-149098). The resin composition is a resin composition comprising the following: (A) a polyphenylene ether resin having a functional group containing a carbon-carbon double bond at the end, and (B) a compound having an isocyanuric acid ring structure and 2 allyl groups in one molecule and being liquid at 25°C. After further in-depth research on such a resin composition, the present inventors found that by setting the end of the polyphenylene ether resin used as component (A) to a group shown in the above formula (1), in particular, the heat resistance and heat resistance reliability of the resin composition are significantly improved, thereby completing the present invention.
[0033] As the compound as (B) component, as mentioned above, it is a compound with isocyanuric acid ring structure and 2 allyl groups in 1 molecule, which can reduce the melt viscosity of resin combination and improve the embedding property of wiring. In addition, as the compound as (B) component, by having 2 allyl groups, extremely good low dielectric properties can be obtained. And, the resin combination of the present embodiment can obtain high heat resistance and heat-resistant reliability by making such (A) component and (B) component cross-linked and cured.
[0034] In addition, the resin composition of the present embodiment may contain other components such as (C) thermoplastic resin, (D) inorganic filler, (E) curing catalyst, etc. in addition to the above-mentioned (A) component and (B) component. Hereinafter, each of the above-mentioned components may be appropriately referred to as (C) component to (E) component.
[0035] [(A) ingredient] The component (A) is a polyphenylene ether resin having a group represented by the above formula (1) at the end. The component (A) is not particularly limited as long as it has a group represented by the above formula (1) at its end and has a polyphenylene ether in its skeleton. By containing the component (A), heat resistance and heat resistance reliability can be extremely effectively improved. Hereinafter, the polyphenylene ether resin having a group represented by the above formula (1) as the component (A) is sometimes referred to as a modified polyphenylene ether. The modified polyphenylene ether of the component (A) is preferably a thermosetting resin.
[0036] In the above formula (1), R 1 represents a hydrogen atom or an alkyl group. 1 The alkyl group is preferably an alkyl group having 1 to 3 carbon atoms, and more preferably an alkyl group having 1 carbon atom. Specific examples thereof include a methyl group, an ethyl group, and a propyl group.
[0037] Examples of the group represented by formula (1) include an acrylate group and a methacrylate group.
[0038] The modified polyphenylene ether having a group represented by the formula (1) has a polyphenylene ether chain in the molecule, and preferably has a repeating unit represented by the following structural formula (3) in the molecule, for example.
[0039] [Chemistry 4]
[0040] In the above structural formula (3), m represents 1 to 50. In addition, R 22 ~R 25 They are independent of each other and can be the same or different from each other. 22 ~R 25 It represents a hydrogen atom or an alkyl group.
[0041] R22 ~R 25 The alkyl group in is not particularly limited, and is preferably an alkyl group having 1 to 8 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms. Specific examples thereof include methyl, ethyl, propyl, hexyl, and octyl groups.
[0042] As the modified polyphenylene ether having the group represented by the above formula (1), for example, a modified polyphenylene ether having the group represented by the above formula (1) at the end of a polyphenylene ether represented by the following formula (4) or formula (5) can be cited. As the modified polyphenylene ether, specifically, a modified polyphenylene ether represented by the following formula (6) or formula (7) can be cited.
[0043] [Chemistry 5] [Chemistry 6] [Chemistry 7] [Chemistry 8]
[0044] In formulae (4) to (7), regarding s and t, for example, the total value of s and t is preferably 1 to 30. In addition, s is preferably 0 to 20, and t is preferably 0 to 20. That is, it is preferred that s represents 0 to 20, t represents 0 to 20, and the total value of s and t represents 1 to 30. In formulae (4) to (7), Y represents an alkylene group having 1 to 3 carbon atoms or a direct bond, and examples of the alkylene group include dimethylmethylene and the like. In formulae (6) and (7), R 1 With R in the above formula (1) 1 The same represents a hydrogen atom or an alkyl group. The alkyl group is not particularly limited, and is preferably an alkyl group having 1 to 3 carbon atoms, and more preferably an alkyl group having 1 carbon atom. Specifically, for example, methyl, ethyl, propyl, and the like can be cited.
[0045] The number average molecular weight (Mn) of the modified polyphenylene ether having a group represented by formula (1) is not particularly limited. Specifically, it is preferably 500 to 5000, more preferably 800 to 4000, and further preferably 1000 to 3000. Here, the number average molecular weight can be any value measured by a conventional molecular weight determination method, and specifically, a value measured using gel permeation chromatography (GPC) can be cited. In addition, in the case where the modified polyphenylene ether having a group represented by formula (1) has a repeating unit represented by formula (3) in the molecule, m is preferably a value such that the weight average molecular weight of the modified polyphenylene ether is within the above range. Specifically, m is preferably 1 to 50.
[0046] If the number average molecular weight of the modified polyphenylene ether having the group represented by formula (1) is within the above numerical range, it has excellent dielectric properties derived from polyphenylene ether and excellent embedding property in the substrate. For example, in the existing polyphenylene ether, if its number average molecular weight is within the above numerical range, the molecular weight is relatively low, and there is a tendency for excellent embedding property in the substrate. On the other hand, the modified polyphenylene ether having the group represented by formula (1) above can improve the heat resistance and heat resistance reliability of the cured product because it has the group represented by formula (1) at the end.
[0047] In addition, in the modified polyphenylene ether used as component (A), the average number of groups represented by the above formula (1) per molecule of modified polyphenylene ether at the molecular end (number of terminal functional groups) is not particularly limited. Specifically, it is preferably 1 to 5, more preferably 1 to 3, and further preferably 1.5 to 3. If the number of terminal functional groups is too small, the curability deteriorates, and there is a tendency to be difficult to obtain a cured product with sufficient strength, adhesion, and heat resistance. In addition, if the number of terminal functional groups is too large, the reactivity becomes too high, and undesirable conditions such as reduced storage of the resin composition, reduced fluidity of the resin composition, brittleness of the cured product, and reduced adhesion may occur. That is, if such a modified polyphenylene ether is used, the following problems may arise: for example, forming defects such as voids are generated during multilayer forming, cracking or interlayer peeling of the substrate becomes prone to occur, and it is difficult to obtain a printed wiring board with high reliability.
[0048] Regarding the number of terminal functional groups of the above-mentioned modified polyphenylene ether, the numerical value represented by the following average value can be cited, and the average value is the average value of the group represented by the above formula (1) per molecule of all modified polyphenylene ethers present in 1 mol of modified polyphenylene ether. The number of terminal functional groups can be determined, for example, by measuring the number of hydroxyl groups remaining in the obtained modified polyphenylene ether and calculating the reduction compared with the number of hydroxyl groups of the polyphenylene ether before modification. The reduction compared with the number of hydroxyl groups of the polyphenylene ether before modification is the number of terminal functional groups. In addition, the method for determining the number of hydroxyl groups remaining in the modified polyphenylene ether can be obtained by adding a quaternary ammonium salt (tetraethylammonium hydroxide) associated with the hydroxyl group to the solution of the modified polyphenylene ether and measuring the UV absorbance of the mixed solution.
[0049] The method for synthesizing the modified polyphenylene ether used as the component (A) is not particularly limited as long as a modified polyphenylene ether having a group represented by the above formula (1) at a terminal can be synthesized.
[0050] As the component (A), the modified polyphenylene ether having a group represented by the above formula (1) at the terminal may be used alone or in combination of two or more modified polyphenylene ethers having a group represented by the above formula (1) at the terminal.
[0051] About the content of (A) component in the resin composition, there is no particular restriction, but relative to the total of 100 parts by mass of the resin component, preferably containing 10 parts by mass to 50 parts by mass of (A) component, further preferably containing 20 parts by mass to 45 parts by mass, particularly preferably containing 25 parts by mass to 40 parts by mass. If the content of (A) component in the total of 100 parts by mass of the resin component is within this range, there is the advantage that the curability is good, the flexibility of the resin composition, the heat resistance of the cured product, the processability of film formation, etc. are improved, the toughness of the cured product is not lost, and the adhesion is not reduced. In addition, the content of (A) component in the resin component can be measured by methods such as infrared spectrophotometer (FTIR), gas chromatography-mass spectrometry analysis, etc. As the resin component in the resin composition, in particular, (A) component, (B) component and (C) component as an arbitrary component can be cited. Therefore, the content of component (A) can be calculated relative to 100 parts by weight of the total of the resin components in the resin composition, for example, relative to 100 parts by weight of the total of the components (A), (B), and (C). In addition, the content of component (B) described later can also be calculated relative to 100 parts by weight of the total of the resin components.
[0052] As the modified polyphenylene ether having a group represented by the above formula (1) at the terminal of the component (A), there can be mentioned "Noryl SA9000" (trade name) manufactured by SABIC Invitrogen Plastics Co., Ltd.
[0053] [(B) ingredient] Component (B) is a compound having an isocyanuric acid ring structure and 2 allyl groups in 1 molecule and being liquid at 25°C. By containing component (B), the melt viscosity of the resin composition can be reduced and the embedding property of the wiring can be improved. In addition, the compound as component (B) can obtain extremely good low dielectric properties by having 2 allyl groups. For example, when a compound having an isocyanuric acid ring structure and 3 allyl groups in 1 molecule is used to replace component (B), sufficient low dielectric properties cannot be obtained. It is speculated that when a compound having 3 allyl groups is used, a three-dimensional cross-linked structure is formed, making the dielectric properties insufficient. On the other hand, if it is a compound having a bifunctional allyl group as component (B) of the resin composition of the present embodiment, a linear cross-linked structure is formed, indicating that the dipole moment of the scale of molecular polarization becomes smaller, so it is estimated that low dielectric properties can be obtained. By making component (B) have an isocyanuric acid ring structure, it is estimated that the heat resistance and heat-resistant reliability of the resin composition can be improved. In addition, embedding property is improved by using a compound that is liquid at 25° C. as the component (B) of the resin composition of the present embodiment. On the other hand, when a compound that is solid at 25° C. is used as the component (B), embedding property is deteriorated, which is not preferred.
[0054] The molecular weight of the component (B) is preferably 300 to 400, more preferably 320 to 400. When the molecular weight of the component (B) is within the above range, excellent dielectric properties and fluidity are achieved.
[0055] (B) The component is preferably a compound represented by the following formula (2).
[0056] [Chemistry 9]
[0057] In the above formula (2), R 2 The alkyl group is an alkyl group having 4 to 14 carbon atoms, preferably an alkyl group having 8 to 14 carbon atoms, and particularly preferably an alkyl group having 10 to 12 carbon atoms.
[0058] Relative to 100 parts by mass of (A) component, the content of (B) component is preferably 20 parts by mass to 80 parts by mass. By constituting in this way, the melt viscosity of the resin composition can be reduced, the embedding property of the wiring can be good, and the heat resistance and heat-resistant reliability can also be improved. In addition, although not particularly limited, relative to 100 parts by mass of (A) component, the content of (B) component is more preferably 25 parts by mass to 75 parts by mass, and further preferably 30 parts by mass to 70 parts by mass.
[0059] In the total 100 mass parts of the resin component of the resin combination, preferably contain 3 mass parts ~ 40 mass parts of (B) component, further preferably contain 5 mass parts ~ 30 mass parts, particularly preferably contain 10 mass parts ~ 25 mass parts. If the containing ratio of (B) component in the total 100 mass parts of the resin component is within the range, the melt viscosity of the resin combination can be reduced, the embedding property of the wiring can be good, and the heat resistance and heat-resistant reliability of the cured product are not reduced, and the dielectric properties are not deteriorated. In addition, the content of (B) component, the content in the resin component, for example, can be measured by methods such as infrared spectrophotometer (FTIR), gas chromatography-mass spectrometry.
[0060] (B) The compound having an isocyanuric acid ring structure and two allyl groups in one molecule and being liquid at 25°C includes "L-DAIC" (trade name) manufactured by Shikoku Chemicals Co., Ltd.
[0061] [(C) ingredient] (C) component is a thermoplastic resin. The thermoplastic resin as component (C) is not particularly limited, but is preferably a thermoplastic elastomer having a dielectric loss tangent (tanδ) of less than 0.005 in the frequency range of 1 GHz to 100 GHz. Thus, it is possible to contribute to the excellent dielectric properties of the thermosetting film formed by the resin composition of the present embodiment in the high frequency range. As a "thermoplastic elastomer having a dielectric loss tangent (tanδ) of less than 0.005 in the frequency range of 1 GHz to 100 GHz", a styrene-based thermoplastic elastomer is preferred. As a styrene-based thermoplastic elastomer, for example, a block copolymer containing a block of styrene or its analogue as at least one terminal block and an elastomer block containing a conjugated diene as at least one middle block can be cited. For example, styrene / butadiene / styrene block copolymer (SBS), styrene / butadiene / butylene / styrene block copolymer (SBBS), styrene / ethylene / butylene / styrene block copolymer (SEBS), styrene / ethylene / ethylene / propylene / styrene block copolymer (SEEPS), etc. By containing a styrene-based thermoplastic elastomer, it is possible to impart flexibility to the resin composition, maintain the toughness of the cured product, improve adhesion, and reduce dielectric properties.
[0062] The thermoplastic resin of component (C) is more preferably styrene / ethylene / butylene / styrene block copolymer (SEBS), styrene / ethylene / ethylene / propylene / styrene block copolymer (SEEPS), etc. By including such a styrene-based thermoplastic elastomer as component (C), since it is a hydrogenated styrene-based thermoplastic elastomer, the dielectric properties are improved and the heat-resistant reliability can be improved (the change rate of the dielectric loss tangent (tan δ) is reduced).
[0063] There is no particular restriction on the content of component (C), but when containing component (C), in a total of 100 parts by mass of the resin components of the resin composition, preferably 20 to 80 parts by mass of component (C), more preferably 30 to 70 parts by mass, and further preferably 40 to 60 parts by mass. By making the content of component (C) within this range, the heat-resistant reliability of the resin composition can be improved (reducing the rate of change of dielectric loss tangent (tan δ)), and further improving the soldering heat resistance.
[0064] The number average molecular weight of the thermoplastic resin of the component (C) is preferably 30,000 or more, more preferably 40,000 or more, and further preferably 50,000 or more. In addition, the number average molecular weight of the thermoplastic resin of the component (C) is preferably 30,000 to 150,000, more preferably 40,000 to 120,000, and particularly preferably 50,000 to 100,000. By making the number average molecular weight within this range, the soldering heat resistance is improved. In addition, the thermoplastic resin of the component (C) has a tendency that the higher the molecular weight, the higher the melt viscosity of the resin composition and the worse the embedding property to the substrate. However, by containing a compound having an isocyanuric acid ring structure and two allyl groups in one molecule and being liquid at 25°C, namely, the component (B), even when a thermoplastic resin with a large molecular weight is used, the melt viscosity of the resin composition can be reduced and the embedding property to the wiring can be improved.
[0065] [(D) ingredient] (D) component is an inorganic filler. Insulation and low thermal expansion coefficient are required for the inorganic filler. As the inorganic filler, a general inorganic filler can be used. For example, as the inorganic filler, silicon dioxide, aluminum oxide, aluminum nitride, calcium carbonate, aluminum silicate, magnesium silicate, magnesium carbonate, barium sulfate, barium carbonate, calcium sulfate, aluminum hydroxide, calcium silicate, potassium titanate, titanium oxide, zinc oxide, silicon carbide, silicon nitride, boron nitride, etc. can be cited. The inorganic filler can be used alone or in combination of two or more. In particular, from the viewpoint of low thermal expansion coefficient and low dielectric properties, a silica filler is preferred.
[0066] Inorganic filler can be surface treated by silane coupling agent having one or more functional groups selected from acrylic acid group, methacrylic acid group, styryl, amino, epoxy group, vinyl, urea group, mercapto group, isocyanate group, sulfide group, or by silane coupling agent with long chain hydrocarbon group. For example, inorganic filler is preferably surface treated with aminosilane coupling agent, urea group silane coupling agent, epoxy group silane coupling agent, mercapto group silane coupling agent, vinyl group silane coupling agent, styryl group silane coupling agent, (methyl) acrylate silane coupling agent, isocyanate group silane coupling agent, sulfide silane coupling agent, octyl group silane coupling agent, octenyl group silane coupling agent, further organic silazane compound (オルガノシラザン compound), titanate group coupling agent and other surface treatment agents, so as to improve its moisture resistance, dispersibility, etc. They can use one or more in combination. More preferably, among the surface-treated silica fillers, it is preferred to use a silica filler surface-treated by a vinyl silane coupling agent. By using a silica filler surface-treated by a vinyl silane coupling agent, it is possible to react with component (A) and component (B) to make the toughness and adhesion of the cured product good. In addition, it is preferred to use a silica filler surface-treated with a silane coupling agent having a long-chain hydrocarbon group. By using a silica filler surface-treated with a silane coupling agent having a long-chain hydrocarbon group, the moisture resistance of the cured product can be improved.
[0067] The shape of the inorganic filler is not particularly limited, and spherical, flaky, needle-shaped, irregular shapes, etc. can be cited. From the viewpoint of the high filling property, dispersibility, fluidity of the resin composition, and low thermal expansion coefficient of the cured product of the inorganic filler, a spherical shape is preferred. The average particle size is preferably 0.05 μm to 20 μm, more preferably 0.1 μm to 15 μm, and further preferably 0.5 μm to 10 μm. By making the average particle size of the inorganic filler in this range, the embedding property between the microstructures of the substrate and electronic components is excellent. In addition, the resin composition can be made into a thin film. The average particle size is the particle size at the cumulative value of 50% in the particle size distribution based on the volume basis measured by the laser diffraction scattering method. The average particle size can be measured, for example, by a laser scattering diffraction particle size distribution measuring device: LS13320 (manufactured by Beckman Colter, wet type).
[0068] In the case of containing (D) component, there is no particular limitation, but in the non-volatile component 100% by mass in the resin composition, it is preferred to contain 50% by mass or more of (D) component, more preferably 60% by mass or more, and further preferably 65% by mass or more. By constituting in this way, the thermal expansion coefficient can be reduced. More specifically, by making the content ratio of (D) component within the above range, the linear expansion coefficient α1 of the cured product of the resin composition when it is less than the glass transition temperature and the linear expansion coefficient α2 of the cured product when it is above the glass transition temperature can be reduced. In addition, in the non-volatile component 100% by mass in the resin composition, it is preferred to contain 50% by mass to 95% by mass of (D) component, more preferably 60% by mass to 90% by mass, and further preferably 65% by mass to 85% by mass. By making the content ratio of (D) component within the above range, the linear expansion coefficient α2 above the glass transition temperature can be reduced, and the generation of stress during the heat-resistant reliability test of the multilayer substrate can also be reduced.
[0069] In addition, in order to reduce the thermal expansion coefficient of the resin composition, as described above, when the (D) component is contained at 50% by mass or more, if the filling amount of the inorganic filler is high, there is a tendency that the melt viscosity of the resin composition becomes high and the embedding property into the substrate becomes poor. However, by containing a compound having an isocyanuric acid ring structure and two allyl groups in one molecule and being liquid at 25°C, that is, the (B) component, even when the filling amount of the inorganic filler is high, the melt viscosity of the resin composition can be reduced and the embedding property into the wiring can be improved.
[0070] As the silica filler used for component (D), fused silica, ordinary silica, spherical silica, crushed silica, crystalline silica, amorphous silica, etc. can be cited without particular limitation. From the viewpoints of the dispersibility of the silica filler, the fluidity of the thermosetting resin composition, the surface smoothness of the cured product, the dielectric properties, the low thermal expansion coefficient, the adhesion, etc., spherical fused silica is ideal.
[0071] The method for surface-treating the silica filler using the coupling agent is not particularly limited, and examples thereof include a dry method and a wet method.
[0072] The dry method is a method of surface treatment by placing a silica filler and a silane coupling agent in an appropriate amount relative to the surface area of the silica filler in a stirring device and stirring under appropriate conditions, or placing the silica filler in a stirring device in advance, stirring under appropriate conditions, and adding a silane coupling agent in an appropriate amount relative to the surface area of the silica filler in the form of a stock solution or solution by dropping or spraying, etc., stirring to make the silane coupling agent uniformly adhere to the surface of the silica filler, and performing surface treatment (by hydrolyzing it). The stirring device is not particularly limited, and for example, a mixer that can stir and mix by high-speed rotation, such as a Henshell mixer, can be cited.
[0073] The wet method is a method for performing surface treatment by dissolving a sufficient amount of silane coupling agent relative to the surface area of the silica filler to be surface treated in water or an organic solvent to obtain a surface treatment solution, adding the silica filler to the surface treatment solution, stirring to form a slurry, thereby allowing the silane coupling agent and the silica filler to fully react, and then separating the silica filler from the surface treatment solution by filtration or centrifugal separation, and heating and drying, thereby performing surface treatment.
[0074] [(E) ingredient] (E) component is a curing catalyst. The curing catalyst as component (E) is an additive for causing the reaction of component (A) and component (B) well. By containing such component (E), the degree of cure of the resin composition relative to a certain curing temperature and time can be improved. Therefore, the resin composition of the present embodiment preferably further contains a curing catalyst as component (E).
[0075] The curing catalyst of component (E) may be any catalyst that initiates the curing reaction of components (A) and (B), and a conventionally known reaction initiator (e.g., a polymerization initiator) may be used. For example, organic peroxides, azo compounds, etc. may be cited as curing catalysts. Organic peroxides manufactured by NOF Corporation, trade names "Parkmil D" and "Parbcil C", etc. may be cited as curing catalysts of component (E). Component (E) may be used alone or in combination of two or more.
[0076] In addition, when containing (E) component, the content of (E) component is preferably 0.1 to 5 parts by mass relative to the total 100 parts by mass of the resin component of the resin composition. By constituting in this way, heat resistance and adhesion can be well improved. In addition, the content of (E) component is not particularly limited, but is more preferably 0.1 to 4 parts by mass, and further preferably 0.1 to 3 parts by mass relative to the total 100 parts by mass of the resin component of the resin composition.
[0077] [(F)INGREDIENT] The component (F) is an antioxidant. The antioxidant of the component (F) is an additive for improving heat resistance reliability. By including such a component (F), heat resistance reliability can be improved.
[0078] [(G) ingredient] The component (G) is a silane coupling agent. By adding the silane coupling agent as the component (G), the adhesiveness can be improved.
[0079] [Other ingredients] The resin composition of the present embodiment may further contain components other than the components (A) to (E) described above. For example, other components include various additives such as solvents, dispersants, defoamers, leveling agents, thixotropic agents, flame retardants, and fluxes.
[0080] [Method for producing resin composition] The resin composition of the present embodiment can be manufactured by a conventional method. The resin composition of the present embodiment can be manufactured by dissolving, mixing and dispersing the components described above together with a solvent using, for example, a bead mill, a pounder, a pot mill, a three-roll mill, a rotary mixer, a double-shaft mixer, a dissolver, a stirrer, etc.
[0081] [Application of resin composition] The resin combination of the present embodiment can be suitably used as the resin combination for the protective agent, adhesive, and adhesive film used in the electronic component. In addition, the resin combination of the present embodiment can also be suitably used as an interlayer bonding bonding sheet or interlayer adhesive for a multilayer wiring substrate. When the resin combination of the present embodiment is used for various purposes of electronic components, there is no particular restriction on the electronic component as the bonding object, and various printed wiring substrates such as ceramic substrates or organic substrates, various electronic components, semiconductor chips, semiconductor devices, etc. can be cited.
[0082] The adhesive film, interlayer adhesive sheet, and interlayer adhesive using the resin composition of the present embodiment are contained in a laminate or semiconductor device constituting an electronic component as a cured product of the resin composition. Therefore, the laminate or semiconductor device constituting an electronic component preferably contains a cured product of the resin composition of the present embodiment.
[0083] Furthermore, the resin composition of the present embodiment can also be used as a prepreg using the resin composition or a high-frequency electronic component having a cured product of the resin composition.
[0084] [Elastic modulus at room temperature (25°C)] The elastic modulus of the resin composition of the present embodiment at room temperature (25°C) is preferably 1.0GPa to 15.0GPa, more preferably 1.5GPa to 12.0GPa, further preferably 2.0GPa to 10.0GPa, and particularly preferably 4.1GPa to 9.0GPa. By making the elastic modulus at 25°C within the above range, a cured product having a high hardness and a hard surface that is not easily scratched can be obtained. On the other hand, when the elastic modulus is lower than the above range, the cured product is soft, and in the process of manufacturing the wiring substrate, the cured product may sometimes be scratched or broken.
[0085] [Elastic modulus at 200°C] From the viewpoint of reducing stress and strain generated during heating, the elastic modulus of the resin composition of the present embodiment at 200° C. is preferably 0.1 GPa to 5.0 GPa, more preferably 0.1 GPa to 3.0 GPa, and even more preferably 0.1 GPa to 2.0 GPa.
[0086] [Glass transition temperature (Tg)] The glass transition temperature of the resin composition of the present embodiment is preferably 120°C to 170°C, more preferably 130°C to 165°C, further preferably 135°C to 160°C, and particularly preferably 140°C to 158°C. By making the glass transition temperature within the above range, a cured product having flexibility that can follow the degree of deformation and good impact resistance can be obtained. When the glass transition temperature is higher than the above range, the cured product tends to become brittle, and in the process of manufacturing the wiring substrate, the cured product may sometimes be scratched, notched, cracked, or otherwise damaged. On the other hand, when the glass transition temperature is lower than the above range, the stress generated during the reliability test (e.g., hot and cold cycle test) of the multilayer substrate becomes larger, and problems may sometimes occur during the reliability test. Example
[0087] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples. In the following examples, parts and % represent parts by mass and % by mass unless otherwise specified.
[0088] (Example 1 to Example 16, Comparative Example 1 to Comparative Example 5) [Sample production] After measuring the components except component (D) and component (E) according to the proportions (parts by mass) shown in Tables 1 to 5 below, put them into a container for dissolving together with a specified solvent, stir them at a rotation speed of 100 rpm to 400 rpm using a stirrer with the lid closed, and heat to 70°C and mix at normal pressure for 3 to 6 hours. After that, cool to room temperature, add component (D), stir and mix at a rotation speed of 100 rpm to 400 rpm for 1 hour, and then disperse using a bead mill. After that, add component (E), stir and mix at a rotation speed of 100 rpm to 400 rpm for 1 hour using a stirrer. As described above, a dissolved dispersion of the resin composition containing Examples 1 to 16 and Comparative Examples 1 to 5 was prepared.
[0089] In Examples 1 to 16 and Comparative Examples 1 to 5, the raw materials used to prepare the dissolved dispersion containing the resin composition are as follows.
[0090] [(A) ingredient] (A1): a polyphenylene ether resin having a group represented by the formula (1) at the terminal, manufactured by SABIC Invitrogen Plastics Co., Ltd., trade name “Noryl SA9000”, Mn: 1850-1950. [(A')Component] (A'2): a polyphenylene ether resin having no group represented by the formula (1) at the terminal, manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "OPE-2St 2200", Mn: 2200.
[0091] [Component (B): a compound having an isocyanuric acid ring structure and two allyl groups in one molecule] (B1): manufactured by Shikoku Chemicals Co., Ltd., trade name "L-DAIC", a compound represented by the above formula (2). In the above formula (2), R 2 It is an alkyl group having 4 to 14 carbon atoms. [Component (B'): a compound other than component (B) having an allyl group in one molecule] (B'2): A compound having an isocyanuric acid ring structure and three allyl groups in one molecule, manufactured by Mitsubishi Chemical Corporation and trade name "TAIC".
[0092] [Component (C): thermoplastic resin] (C1): Hydrogenated styrene-based thermoplastic elastomer (SEBS) manufactured by Corner Materials Co., Ltd., trade name "Colortron G1652", Mn: 54,000. (C2): Hydrogenated styrene-based thermoplastic elastomer (SEEPS) manufactured by Kuraray Co., Ltd., trade name "SEPTON 4033", Mn: 74,000. (C3): Hydrogenated styrene-based thermoplastic elastomer (SEBS) manufactured by Kuraray Corporation, trade name "Septone 8004", Mn: 76,000.
[0093] [Component (D): Inorganic filler] (D1): Spherical silica (spherical silica used was manufactured by Denka Corporation, trade name “FB-3SDX (average particle size: 3 μm)”) surface-treated with 7-octenyltrimethoxysilane (a silane coupling agent manufactured by Shin-Etsu Chemical Co., Ltd. (trade name “KBM-1083”)). (D2): Spherical silica (spherical silica used was manufactured by Denka, trade name “FB-3SDX (average particle size: 3 μm)”) surface-treated with octyltriethoxysilane (a silane coupling agent manufactured by Shin-Etsu Chemical Co., Ltd. (trade name “KBE-3083”)). (D3): Spherical silica whose surface was not treated with a silane coupling agent (the spherical silica used was "FB-3SDX (average particle size: 3 μm)" manufactured by DENKA Corporation). (D4): Spherical silica surface-treated with a silane coupling agent KBM-1003 (product name “10SV-C12 (average particle size 1 μm)” manufactured by Admatex Corporation was used). (D5): Spherical silica surface-treated with the silane coupling agent KBM-1083 (trade name “20SV-C9 (average particle size 2 μm)” manufactured by Admatex Corporation was used).
[0094] [Component (E): Curing Catalyst] (E1): Manufactured by NOF Corporation, trade name "パークミルD".
[0095] [Ingredient (F): Antioxidant] (F1): Hindered phenol antioxidant manufactured by ADEKA Corporation (melting point: 220° C. to 222° C.), trade name “AO-20”. (F2): Hindered phenol antioxidant manufactured by ADEKA Corporation (melting point 51° C. to 54° C.), trade name “AO-50”.
[0096] [Component (G): silane coupling agent] (G1): A silane coupling agent (bis(triethoxysilylpropyl)tetrasulfide) manufactured by Osaka Soda Co., Ltd., trade name "Cablas 4".
[0097] In addition, the "resin component total" column of Tables 1 to 4 shows the total amount (mass parts) of the components corresponding to the resin component in the raw materials used to prepare the resin composition. In addition, the "solid content total" column of Tables 1 to 4 shows the total amount (mass parts) of the components corresponding to the solid content in the raw materials used to prepare the resin composition. The "filler ratio (Wt%)" column of Tables 1 to 4 shows the ratio (mass %) of the (D) component in the solid content raw materials used to prepare the resin composition.
[0098] For the dissolved dispersion containing the resin composition of Examples 1 to 11 and Comparative Examples 1 to 5 obtained in the above manner, the "heat resistance reliability", "soldering heat resistance" and "substrate pattern embedding property" were evaluated and measured by the methods shown below. In addition, in each evaluation and measurement, a resin film was prepared by the following method, and the prepared resin film was used as the object of evaluation and measurement. First, a dissolved dispersion containing each resin composition was applied on a PET film that had been subjected to a peeling treatment by a scraper method. Thereafter, the dissolved dispersion on the PET film was dried at a temperature of 80°C to 130°C to prepare a resin film with a thickness of 50μm to 100μm. The results are shown in Tables 1 to 4.
[0099] [Heat resistance reliability] [Initial values (relative dielectric constant (ε) and dielectric loss tangent (tanδ))] The resin film prepared by the above method is cured under the conditions of temperature 200 ° C, 1 hour and pressure 1 MPa to prepare a sample for measuring relative dielectric constant (ε) and dielectric loss tangent (tan δ). For the prepared sample, the relative dielectric constant (ε) and dielectric loss tangent (tan δ) are measured using a 10 GHz resonator of the SPDR method. The relative dielectric constant (ε) is preferably less than 3.50, more preferably less than 3.25. In addition, the dielectric loss tangent is preferably less than 0.003, more preferably less than 0.002.
[0100] [After 125°C × 1000 hours and the rate of change from the initial value (%) (relative dielectric constant (ε) and dielectric loss tangent (tanδ))] After the resin film for which the above-mentioned dielectric properties (initial values) were measured was placed at 125°C for 1000 hours, the relative dielectric constant (ε) and dielectric loss tangent (tanδ) after 125°C × 1000 hours were measured using a 10 GHz resonator of the SPDR method at normal temperature and humidity. For the relative dielectric constant (ε) and dielectric loss tangent (tanδ) measured after 125°C × 1000 hours, the rate of change (%) relative to the initial value was calculated. In addition, the rate of change (%) relative to the initial value is the value (%) obtained by dividing the difference between each measured value and the initial value after 1000 hours by the initial value and then multiplying by 100.
[0101] [Soldering heat resistance (280℃, 290℃, 300℃)] The resin film made by the above method is clamped with a copper foil having a thickness of 18 μm, and solidified under the conditions of temperature 200 ° C, 1 hour, and pressure 3MPa to prepare a sample (double-sided copper clad laminate) for evaluating soldering heat resistance. The produced double-sided copper clad laminate is cut into a block of 25 mm square, and floated in a solder bath of 280 ° C, 290 ° C and 300 ° C for 1 minute, during which the appearance of each sample is visually confirmed, and evaluated based on the following evaluation criteria. The situation where the evaluation result is "0" is considered qualified. ○: No change. ×: Swelling and peeling of copper foil were observed.
[0102] [Substrate pattern embedding properties] Using FR4 (manufactured by Panasonic Corporation) with a thickness of 0.1 mm and a copper foil thickness of 35 μm, a general method such as Figure 1 The substrate for embedding property evaluation was prepared by patterning as shown. Figure 1 It is a plan view showing patterning in the evaluation of embedding property of a substrate pattern. Figure 1 L / S in represents line and space (ラインアンドスペース).
[0103] Secondly, the resin film and copper foil (18μm) were cut into 100mm×100mm, and layered in the order of copper foil, resin film, substrate for embedding evaluation, resin film, and copper foil. After curing at 200°C, 1 hour, and a pressure of 3MPa, only one side of the copper foil was etched away to expose the surface of the resin film, and the embedding property was evaluated by observing its appearance.
[0104] Examples of photos showing good embedding performance Figure 2 As shown in the picture, the embedding performance is poor. Figure 3 As shown. Figure 3As shown in FIG. 1 , when the embedding property is poor and there is a portion between the patterns where the resin film is not embedded (poor embedding site), the color of the poor embedding site is observed to be mottled and white. The case where the evaluation result is "0" is considered to be acceptable. ○: No implantation failure was observed. ×: A poorly embedded portion was observed.
[0105] In addition, the "elastic modulus at room temperature (25°C)", "elastic modulus at 200°C" and "glass transition point (Tg)" were evaluated and measured for the dissolved dispersions containing the resin compositions of Examples 7 and 12 to 16 by the following methods. The evaluation results are shown in Table 5.
[0106] 《Evaluation of elastic modulus》 The measurement was performed by dynamic viscoelasticity measurement (DMA). Specifically, the film was heat-cured at 200°C, and after peeling off from the support, a test piece (10±0.5mm×40±1mm) was cut out from the adhesive film, and the width and thickness of the test piece were measured. Afterwards, the measurement was performed by DMS6100 (3°C / min 23°C-250°C 10Hz). The storage elastic modulus at 25°C was taken as the "elastic modulus at room temperature (25°C)", and the storage elastic modulus at 200°C was taken as the "elastic modulus at 200°C".
[0107] 《Glass transition temperature (Tg)》 The above-mentioned dynamic viscoelasticity measurement (DMA) was used for measurement. Specifically, the film was cured by heating at 200°C, and after peeling from the support, a test piece (10±0.5mm×40±1mm) was cut out from the adhesive film, and the width and thickness of the test piece were measured. After that, the test piece was measured by DMS6100 (3°C / min 23°C-250°C 10Hz). The peak temperature of tanδ was read as Tg.
[0108] 《Impact resistance》 The falling ball impact strength was measured. Specifically, the film was heated and cured at 200°C to prepare a test piece of 20 mm × 30 mm and 1 mm thick. The test piece was placed on an iron plate, and an alumina ball weighing 25 g was dropped from a height of 50 cm from above to perform an impact resistance test. The test was performed three times, and those that did not crack in any test were considered good.
[0109] [Table 1]
[0110] [Table 2]
[0111] [Table 3]
[0112] [Table 4]
[0113] [Table 5]
[0114] [result] As shown in Tables 1 and 2, for Examples 1 to 10, by using SA-9000 as the (A) component, the change rate of tan δ was 20% or less in terms of heat resistance reliability, and the soldering heat resistance was acceptable and good at 300°C. In addition, by using L-DAIC as the (B) component, the substrate embedding property was acceptable and good.
[0115] Comparative Example 1, in which the component (A) of Example 7 was replaced with OPE-2ST 2200, had a large change rate of tan δ of 58.9% in heat resistance reliability, which was inferior. Comparative Example 2, in which the component (B) of Example 1 was replaced with TAIC, had a large initial value of tan δ of 0.0022, which was higher than 0.002 and was inferior in this respect. In Comparative Example 3, in which the component (A) of Example 1 was replaced with OPE-2ST 2200, the change rate of tanδ was large, 24.1%, which was more than 20%, in terms of heat resistance reliability. In addition, the heat resistance reliability was also unqualified at 280°C, which was poor in this respect. In addition, in Comparative Example 1, which also used OPE-2ST 2200, the soldering heat resistance was also qualified at 300°C, but this was because Comparative Example 3 used Kabura 4, which was the component (G), and therefore the difference in heat resistance between SA-9000 and OPE-2ST 2200 was more significantly manifested. Comparative Example 4, in which L-DAIC as the component (B) was further removed from Comparative Example 3 and the reduced portion was replaced with the component (C), had poor soldering heat resistance as in Comparative Example 3, and furthermore, failed in embedding property into the substrate pattern.
[0116] Table 4 shows the case where the inorganic filler of component (D) is not used. In terms of heat resistance reliability, the change rate of tanδ in Example 11 using SA-9000 as component (A) is 176.8%, while the change rate of tanδ in Comparative Example 5 using OPE-2St 2200 is large, 222.2%, so Example 11 is more excellent. In addition, in terms of solder heat resistance, Example 11 is qualified at 300°C, while Comparative Example 5 is unqualified at 300°C. Regarding substrate pattern embedding properties, since both Example 11 and Comparative Example 5 use L-DAIC as component (B), both are qualified. In addition, regarding the heat-resistant reliability of ε, generally, the change was small, and all the Examples and Comparative Examples were good.
[0117] As shown in Table 5, for Example 7 and Examples 12 to 16, the elastic modulus at room temperature (25°C) was 4.1 GPa to 9.0 GPa or less, and the elastic modulus at 200°C was good, 0.1 GPa to 2.0 GPa or less. In addition, the glass transition temperature of Example 7 and Examples 12 to 16 was in the range of 140°C to 158°C, which was good, and regarding impact resistance, no defects such as cracks were observed in all Examples. Industrial Applicability
[0118] The resin composition of the present invention can be used as an adhesive used in electronic components, a resin composition for adhesive films. In addition, the resin composition of the present invention can be used as an interlayer bonding adhesive sheet and an interlayer adhesive for multilayer wiring substrates. In addition, the resin composition of the present invention can also be used as a prepreg using a cured product of the resin composition, or a high-frequency electronic component having a cured product of the resin composition.
Claims
1. A resin composition, comprising: (A) a polyphenylene ether resin having a group represented by the following formula (1) at the terminal, and (B) a compound having an isocyanuric acid ring structure and two allyl groups in one molecule and being liquid at 25°C, [Chemistry 1] in, In the formula (1), R 1 represents a hydrogen atom or an alkyl group.
2. The resin composition according to claim 1, wherein The component (B) is a compound represented by the following formula (2): [Chemistry 2] Wherein, in the formula (2), R 2 It is an alkyl group having 4 to 14 carbon atoms.
3. The resin composition according to claim 1 or 2, wherein The resin composition further includes (C) a thermoplastic resin having a number average molecular weight of 30,000 or more.
4. The resin composition according to claim 3, wherein The component (C) is a thermoplastic elastomer having a dielectric loss tangent (tan δ) of less than 0.005 in a frequency range of 1 GHz to 100 GHz.
5. The resin composition according to claim 3 or 4, wherein The resin composition contains 20 to 80 parts by mass of the component (C) based on 100 parts by mass of the total resin components.
6. The resin composition according to any one of claims 1 to 5, wherein The resin composition further includes (D) an inorganic filler.
7. The resin composition according to claim 6, wherein The resin composition contains 50% by mass or more of the component (D) based on 100% by mass of nonvolatile components in the resin composition.
8. The resin composition according to claim 7, wherein The resin composition contains 60% by mass to 90% by mass of the component (D) based on 100% by mass of nonvolatile components in the resin composition.
9. The resin composition according to any one of claims 1 to 8, wherein The resin composition further includes (E) a curing catalyst.
10. The resin composition according to any one of claims 1 to 9, wherein The resin composition contains 10 to 50 parts by mass of the component (A) based on 100 parts by mass of the total of the resin components.
11. The resin composition according to any one of claims 1 to 10, wherein The resin composition contains 3 to 40 parts by mass of the component (B) based on 100 parts by mass of the total resin components.
12. A cured product of the resin composition according to any one of claims 1 to 11. 13 . A prepreg comprising the resin composition according to claim 1 . 14 . A printed wiring board comprising a cured layer composed of the resin composition according to claim 1 . 15 . A high-frequency electronic component comprising the cured product according to claim 12 .
Citation Information
Patent Citations
Fluorescent white toners and related methods
JP2021149098A
Thermosetting resin composition and unhardened film composed of the same
WO2008018483A1